Echocardiographic measurements of left atrial volume in patients with ischaemic heart disease. (17th March 2022) - Backman, Marie; Rosfors, Stefan
Abstract: Echocardiographic measurements of left atrial volume (LAV) were evaluated in 57 consecutive patients with ischaemic heart disease. LAV was 38 ml/m 2 (SD 11), larger in patients with ejection fraction (EF) below 45% than in patients with normal EF (≥55%) but in regression analyses only E/e′ correlated independently with LAV. Measurements of LAV had acceptable reproducibility where repeated examinations indicated that half of the variability was explained by the measurement procedure. Our results suggest that an increase or decrease in LAV of 13 ml/m 2 between two examinations indicates a true change in volume, possible due to a changed left ventricular filling pressure.